The marine community of shared destiny driving paradigm shift in vessel pollution governance: an integrated governance framework for sustainable ocean development - Chai, Yuhong; Wu, Yue (Frontiers in Marine Science, 2025)
Within global economic integration, the shipping industry handles over 80% of global trade and is a key driver of economic growth. Consequently, marine vessel pollution control has become an issue of increasing significance. While the International Convention for the Prevention of Pollution from Ships (MARPOL) and related treaties and agreements establish foundational provisions for vessel pollution control, they fall short in addressing the contemporary challenges posed by such pollution. China’s concept of the Marine Community of Shared Destiny (MCSD) offers a novel ideological framework for global ocean governance. Under this framework, a new governance structure for marine vessel pollution control is being established—integrating hard and soft law, shared responsibility, and technological empowerment. This structure aims to transition relevant conventions from voluntary guidelines to mandatory constraints, enhance transparency and credibility through blockchain technology, and ultimately achieve multi-stakeholder governance to establish a new order for controlling marine vessel pollution. The MCSD concept, by creating new systems and using technology, can effectively balance countries’ own interests with the shared interests of the world. It offers a practical reform plan that is both sound in theory and workable in practice. This provides useful guidance for making the shipping industry more environmentally friendly and improving how the world manages shared ocean resources.